Chronic fatigue syndrome in children: a cross sectional survey. Issue 10 (19th September 2003) - Patel, M X; Smith, D G; Chalder, T; Wessely, S
Abstract : Background: Chronic fatigue syndrome (CFS) in children is a controversial diagnosis with unclear aetiology, ill defined but likely increasing incidence, and debatable clinical management options. However these children experience real and considerable suffering. Appropriate research in this clinical population is sparse and usually occurs in tertiary referral units. Methods: Cross sectional survey of 36 children attending a GP specialist interest clinic in southeast England. Results: Patient sociodemographics and clinical morbidity were largely comparable to the literature from tertiary referral research centres. Some prognostic indicators for adults did not readily transfer to this younger age group, although several children had a positive family psychiatric history. Receiving treatment was associated with increased school attendance, but one third of subjects obtained no qualifications. Return to normal health or significant overall improvement was reported by 29/36 subjects. Conclusions: The outcomes in this setting are favourable and comparable to those seen in a controlled setting; this study supports the concept that the prognosis for CFS in children and adolescents is generally good. However, the impact of the illness is significant and this is perhaps most evident in terms of education. Current methods of reporting educational outcomes in the literature are varied and merit development of standardised tools.